New approach to optimize therapy in type 2 diabetes mellitus: the importance of subclassification - Reyes-Medina, María José; Cantón-Habas, Vanesa; Sánchez-Jiménez, Francisco Javier; Molina-Hurtado, Enrique; Carrera-González, María del Pilar (Frontiers in Endocrinology, 2025)
Despite advances in diagnosis, monitoring, and pharmacological treatment, type 2 diabetes mellitus continues to be associated with a high number of serious microvascular and macrovascular complications. The objective of this review was to explore the usefulness of subclassification based on patient pathophysiology, its implementation in clinical practice, and its potential to tailor available treatments based on the patient’s pathophysiological profile, in order to evaluate personalized alternatives that optimize the management of this complex disease. In this sense, patients with recently diagnosed type 2 diabetes mellitus could be grouped into seven subgroups: diabetes with pancreatic β-cell deficiency, insulin-resistant diabetes, patients with a combination of deficient insulin secretion and increased resistance, obesity-related diabetes, patients with obesity and a high level of insulin resistance, age-related diabetes, and diabetes with hereditary components. A new algorithm for the stratified diagnostic classification of type 2 diabetes mellitus is presented. According to the reviewed and currently available studies on oral antidiabetics, some drugs may be more effective than others depending on the patient’s subgroup. We propose the administration of insulin or secretagogues in pancreatic β-cell deficiency, thiazolidinediones, SGLT-2 inhibitors or GLP-1 receptor agonists in insulin resistance, and GIP/GLP-1 receptor agonists, GLP-1 receptor agonists or DPP-4 inhibitors depending on the body mass index and the associated risk of hepatic steatosis. Metformin remains recommended as the first-line universal agent across all patient subgroups.